Programming Languages and Development of Key Competences. Systematic Review - Francisca Tejera-Martínez; David Aguilera; José Miguel Vílchez-González (Universidad Autónoma de Baja California, 2020)
This study endeavors to answer a number of questions regarding programming languages in formal education -in particular, in which educational stages programming languages are used and which programming languages are most widely used. Similarly, the study also seeks to explore the impact of these languages on student learning, and to that end, examines how they influence the development of key competences. A systematic review was conducted of studies indexed in the Web of Science and Scopus databases from 2007 to 2018, in accordance with the PRISMA statement. The results show an emerging interest among the scientific community in programming languages in formal learning environments, while confirming the effectiveness of using programming languages for student competence development.